Critical Evaluation of Independent Curriculum (Review of Learning Methods in the Social Sciences Education Perspective) - Ikra, Ikra; Yamin, Muhammad; Hadiyanti, Hadiyanti; Syahrir, Syahrir (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This article describes an evaluation of social science learning methods in the independent learning education system. Based on the implementation of social studies education subjects as a set of social sciences in the implementation of the independent learning curriculum, there are at least two main problems. First, educational facilities to support learning. Second, teacher resources. These two problems are the problems behind the evaluation of the independent learning system within the framework of learning methods from a social science perspective. This paper uses qualitative methods with the type of library research. Qualitative methods were chosen to obtain data through in-depth and critical analysis of learning methods in social studies subjects in the independent learning education system. The findings from this article are that social studies subjects are a collection of social sciences including history, geography, economics, and sociology and humanities such as aspects of norms, values, language, arts, and culture. Social studies subjects in the independent learning curriculum have undergone changes through adaptation and innovation to contemporary education. Project-based learning methods and models with methods that combine online and face-to-face learning (blended learning). However, because social studies subjects are clustered together with natural sciences in the Pancasila student profile project, the transformation of students' grades tends to favor learning methods outside the classroom with direct practice and the use of a variety of visual media. Therefore, the conclusion of this article is that learning methods in social studies education subjects tend to be directed towards educators or teachers. There are at least two things that need to be evaluated by teachers in implementing the independent learning education system. First, the teacher's capacity to understand the independent learning education system. Second, the social studies learning method guides teachers to learn more outside the classroom with direct practice and the use of various visual media by utilizing technology and the internet. Students tend to get bored with boring lecture learning methods or models.